2020
DOI: 10.1371/journal.pone.0244031
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ecotin homologs from Campylobacter rectus and Campylobacter showae

Abstract: Ecotin, first described in Escherichia coli, is a potent inhibitor of a broad range of serine proteases including those typically released by the innate immune system such as neutrophil elastase (NE). Here we describe the identification of ecotin orthologs in various Campylobacter species, including Campylobacter rectus and Campylobacter showae residing in the oral cavity and implicated in the development and progression of periodontal disease in humans. To investigate the function of these ecotins in vitro, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 86 publications
3
3
0
Order By: Relevance
“…C. upsaliensis and C. helveticus grouped together which is consistent with Stanley et al ( 41 ). C. showae and C. rectus grouped together which is consistent with Thomas et al( 42 ). Several species that occupy unique ecological niches were distantly related to other members of the genus on the phylogenetic tree.…”
Section: Resultssupporting
confidence: 91%
“…C. upsaliensis and C. helveticus grouped together which is consistent with Stanley et al ( 41 ). C. showae and C. rectus grouped together which is consistent with Thomas et al( 42 ). Several species that occupy unique ecological niches were distantly related to other members of the genus on the phylogenetic tree.…”
Section: Resultssupporting
confidence: 91%
“…Here we found that Ecotin is important for STm to survive against both PMN killing mechanisms, granules content and NETs. Similar results were found for ecotin from Campylobacter rectus and Campylobacter showae [34]. We also found that the addition of rEcotin to the NETs prior to the incubation with the Δ eco strain reverted the phenotype to WT levels.…”
Section: Discussionsupporting
confidence: 89%
“…Campylobacter showae (2.40%) was found in nine cases (90%) of PTAP, which has not been found in other countries. It is implicated in the development and progression of periodontal disease (Thomas et al, 2020), and it may play a role in post-treatment endodontic disease. Olsenella uli (2.30%) was detected in 6/10 patients with PTAP, which was also detected in symptomatic endodontic infections of studies in Brazil (Prada et al, 2019;.…”
Section: Discussionmentioning
confidence: 99%